(untitled) (Asian Journal of Plant Biology, 2022)
Acrylamide; a neurotoxicant, is an emerging pollutant of global importance. As a strategy for bioremediation, the breakdown of acrylamide by the action of microbes has seen a gradual but consistent increase in attention all over the world. An acrylamide-degrading bacterium tentatively identified as Bacillus sp. strain UPM2021n was screened for significant parameters contributing to optimized growth on acrylamide using a two-level factorial design. The two-level factorial design was adopted in screening of five independent factors influencing the growth of the bacterium on acrylamide. These factors include pH, temperature, incubation time, acrylamide concentration and glucose concentration. A total of 32 experiments with three replications of the centre points were carried out. The two-level factorial design was successful in finding important contributing parameters in the growth of this bacterium on acrylamide, which were pH and incubation time (p<0.05) that can be further optimized using RSM in future works. The important contributing factors or parameters were analysed using ANOVA, Pareto’s chart and pertubation’s plot and other diagnostic plots. The diagnostic plots such as half-normal, Cook’s distance, residual vs runs, leverage vs runs, Box-Cox, DFFITS, DFBETAS all supported the two-level factorial conclusion with the exception of potentially two outliers that meant the experiment should either be repeated again using blocks or the potential outliers removed from analysis. This significant factors in this study are well within the range reported in many acrylamide-degrading microorganisms. The significant factors obtained in this study will be further processed using Response Surface Method (RSM).